2006
DOI: 10.1016/j.polymdegradstab.2005.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface modification of fillers and polymer on flammability and tensile behaviour of polypropylene-composites

Abstract: An intumescent system consisting of ammonium polyphosphate (APP) as an acid source and blowing agent, pentaerythritol (PER) as a carbonific agent and natural zeolite (clinoptilolite, Go¨rdes II) as a synergistic agent was used in this study to enhance flame retardancy of polypropylene (FR-PP). Zeolite was incorporated into flame retardant formulation at four different concentrations (1, 2, 5, and 10 wt%) to investigate synergism with the flame retardant materials. Filler content was fixed at 30 wt% of total am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…Coagulant temperature ( • C) 25 13 Drying procedure 2 days in water at room temperature 4 h in methanol at room temperature 2 days air dry at room temperature ticle size was 2 m. In order to remove the adsorbed water vapor or other organic vapors, all zeolite particles were dehydrated at 300 • C for 3 h before use.…”
Section: Materials Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulant temperature ( • C) 25 13 Drying procedure 2 days in water at room temperature 4 h in methanol at room temperature 2 days air dry at room temperature ticle size was 2 m. In order to remove the adsorbed water vapor or other organic vapors, all zeolite particles were dehydrated at 300 • C for 3 h before use.…”
Section: Materials Selectionmentioning
confidence: 99%
“…The silicon at the centre is connected to two different functional groups; the organophilic amino group (NH 2 ) and the ethoxy group (C 2 H 5 O). Surface treatment of zeolites with DA silane coupling agent was carried out to produce silanol groups through hydrolysis reaction [13]. Silanol groups, a product of a hydrolysis reaction, react with hydroxyl groups found on zeolite surfaces to form siloxane bonds (-Si-O-zeolite) through a condensation reaction.…”
Section: Characterization Of Polyethersulfone Mixed Matrix Hollow Fibmentioning
confidence: 99%
“…Silane coupling agents have a general formula of YSi(OR) 3 , where R and Y stand for a hydrolysable group (methyl or ethyl) and a non-hydrolysable organofunctional group (amino, methacrylate, mercapto or vinyl groups), capable of interaction with fillers and polymers, respectively [31]. The modification is widely used to control adsorption and catalytic properties of the porous materials of zeolites by inactivation of the external surfaces and reduction of pore size.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the poor water resistance and compatibility with PP matrix of traditional IFR system based on ammonium polyphosphate (APP), melamine and pentaerythritol restrict its application. Demir et al [34] found that surface modification of APP with 3-(trimethoxysilyl)-1-propanethiol coupling agent can improve its water resistance and the compatibility. So, the IFR system based on APP modified with γ-aminopropyltriethoxysilane coupling agent was used as flame retardant in this paper.…”
Section: Introductionmentioning
confidence: 99%